2022
DOI: 10.1002/jcc.27016
|View full text |Cite
|
Sign up to set email alerts
|

Advancing molecular graphs with descriptors for the prediction of chemical reaction yields

Abstract: Chemical yield is the percentage of the reactants converted to the desired products. Chemists use predictive algorithms to select high‐yielding reactions and score synthesis routes, saving time and reagents. This study suggests a novel graph neural network architecture for chemical yield prediction. The network combines structural information about participants of the transformation as well as molecular and reaction‐level descriptors. It works with incomplete chemical reactions and generates reactants‐product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…In addition to product prediction and retrosynthesis where the essence is to define and model the changes in the local structure, works have shown that applying representations based on molecular graphs of reactants, reagents, and the products could be beneficial for more reaction tasks, e.g., yield prediction and condition prediction. , For example, Kwon et al used GNN to embed the reaction into the latent space and then apply variational inference to obtain multiple reaction conditions from the GNN encoded space. Though implementing graphs to represent reactions possesses strength, molecular graphs still have limitations, as they lack critical information such as charges, energies, and steric effects.…”
Section: Mainmentioning
confidence: 99%
“…In addition to product prediction and retrosynthesis where the essence is to define and model the changes in the local structure, works have shown that applying representations based on molecular graphs of reactants, reagents, and the products could be beneficial for more reaction tasks, e.g., yield prediction and condition prediction. , For example, Kwon et al used GNN to embed the reaction into the latent space and then apply variational inference to obtain multiple reaction conditions from the GNN encoded space. Though implementing graphs to represent reactions possesses strength, molecular graphs still have limitations, as they lack critical information such as charges, energies, and steric effects.…”
Section: Mainmentioning
confidence: 99%
“…If we are interested in assessing model performance on new molecules, we can train a model with many reaction templates but use substructure splitting to create training, validation, and testing sets. Bemis-Murcko scaffolds [70] are commonly used to partition the data for this purpose, though clustering based on other input features or chemical similarity to measure extrapolation has also been explored [23,[71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] as has quantifying domains of model applicability [89][90][91][92][93]. Scaffold splitting is not perfect, but by ensuring that molecules in the testing set are structurally different than those in the training set, it offers a much better assessment of generalizability than splitting randomly [17,24,67,[94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109]…”
Section: Interpolation Vs Extrapolationmentioning
confidence: 99%
“…Yarish et al 91 developed the directed message-passing neural network (RD-MPNN) yield prediction models, which they tested on Enamine's proprietary reaction data. Their binary classification model showed a commendable ROC AUC of 0.78.…”
Section: Journal Of Chemical Information and Modelingmentioning
confidence: 99%